2012
DOI: 10.1016/j.yhbeh.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The oxytocin system in drug discovery for autism: Animal models and novel therapeutic strategies

Abstract: Animal models and behavioral paradigms are critical for elucidating the neural mechanism involved in complex behaviors, including social cognition. Both genotype and phenotype based models have implicated the neuropeptide oxytocin (OT) in the regulation of social behavior. Based on the findings in animal models, alteration of the OT system has been hypothesized to play a role in the social deficits associated with autism and other neuropsychiatric disorders. While the evidence linking the peptide to the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
162
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 99 publications
2
162
0
3
Order By: Relevance
“…Alternativ zum Peptidhormon Oxytocin sind synthetische Small-Molecule-Agonisten, welche keine Peptide sind, partielle Agonisten oder Rezeptormodulatoren denkbar, welche die Einschränkungen des Oxytocins umgehen [58]. Die Mehrzahl der Studien beschäftigte sich mit Fragen des Autismus, der Schizophrenie und Angststörungen.…”
Section: Oxytocin In Klinischen Studienunclassified
“…Alternativ zum Peptidhormon Oxytocin sind synthetische Small-Molecule-Agonisten, welche keine Peptide sind, partielle Agonisten oder Rezeptormodulatoren denkbar, welche die Einschränkungen des Oxytocins umgehen [58]. Die Mehrzahl der Studien beschäftigte sich mit Fragen des Autismus, der Schizophrenie und Angststörungen.…”
Section: Oxytocin In Klinischen Studienunclassified
“…Oxytocin, therefore, may be a tool for promoting social behaviors, especially in clinical populations in which social faculties are compromised (8,(11)(12)(13). In the last few years, in fact, oxytocin has been tested in autistic individuals, and it appears to increase social attention and improve emotion recognition (e.g., refs.…”
mentioning
confidence: 99%
“…Only one study to date measured endogenous oxytocin levels in newborns and reported that higher levels of oxytocin in newborns' cerebrospinal fluid (CSF) were associated with higher levels of social engagement, including actively seeking parental social interaction for soothing and a greater interest in social interaction (33). No studies to date, however, have administered oxytocin to infants to determine its effects on social behavior, despite the fact that a more thorough understanding of oxytocin and its behavioral consequences may provide a potential tool for interventions aimed at promoting social affiliation in individuals with social impairments (11)(12)(13)(14)(15)34). The necessity to fill this gap motivated the present study.…”
mentioning
confidence: 99%
“…Oxytocin promotes social behavior, while its deficiency (e.g., oxytocin or oxytocin receptor gene polymorphism) has been implicated in mechanisms of autism [11][12][13]. Oxytocin and oxytocin receptor knockout mice present with autism-like abnormalities [14,15], whereas exogenously administered oxytocin improves autism-like behavior in mice of the BALB/cByJ and C58/J strains [16]. Treatment of Magel-2 deficient mice (which show autism-like impairments over the lifespan) with oxytocin during early postnatal age rescued their social behavior phenotype in the adulthood [48].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies connected autism to the decreased plasma oxytocin levels, as well as to oxytocin receptor gene polymorphism [11][12][13]. In the laboratory setting, oxytocin receptor knockout mice presented with autism-like behavioral impairments [14,15]. Conversely, oxytocin administration improved social behavioral deficits in several models of autism, such as inbred mouse strains BALB/cByJ and C58/J [16].…”
Section: Introductionmentioning
confidence: 99%